Implikasi Kegiatan Remote Sensing terhadap Kedaulatan Negara - Sri Wartini (Jurnal Hukum IUS QUIA IUSTUM, 2000)
A remote sensing provides mankind life with a really big usefulness. However, its application leads a tension for the international community because it deals with the sovereignty of a country. In addition, the remote sensing activities often ignore the country boundaries, that is a country can be remotely sensed without being known by the remotely sensed country. This brings about a serious and controversial debate among developed and developing countries. On the one hand, developing countries desire the developed ones to honor their sovereignty. On the other hand, developing countries want to have the freedom of using outer space.